Trust in Management under Post-bureaucratic Conditions: The Case of Finnish Civil Servants - Koivumäki, Jaakko; Pyöriä, Pasi (Revista Internacional de Organizaciones, 2013)
The Finnish state administration has recently undergone a wave of reforms towards decentralized decision-making and increased flexibility in organizing work. Traditional bureaucracy, however, has its virtues. Based on a survey and qualitative interview material, the results presented in this paper indicate that many characteristics of bureaucracy, such as well-defined work roles and hierarchical control, facilitate trust among employees. In contrast, the current post-bureaucratic model of organizing work may increase insecurity and decrease trust.